Internalized stigmatization and quality of life of patients in a unit of the treatment and education center for alcohol and substance dependence - Türkmen, Sevgi Nehir; Kumaşoğlu, Çiğdem; Akyol, Tuğba (Journal of Dependence, 2015)
Objective: This study was carried out with the aim of determining the levels of internalized stigmatization and quality of life of alcohol or substance dependent patients hospitalized in the Treatment and Education Center for Alcohol and Substance Dependence of Manisa Mental Health Hospital and the psychiatry clinic of Hafsa Sultan Hospital, Celal Bayar University.Methods: The sample of the study was composed of 111 individuals received outpatient treatment between March and June 2014 that fitted the inclusion criteria. The data were collected by Introductory Information form, the Mental Illness Internalized Stigmatization Scale and the WHOQOL BREF Quality of Life Scale. In the analysis of data, percentages, t-test, Mann Whitney U, chisquare and Pearson correlation were used.Results: 93.7 % of the patients were male with a mean age of 30.6 years. It was found that patients over 22 years had higher scores on the internalized stigmatization scale and the subscales of alienation, stereotyping, and social withdrawal than patients less than 22 years. When patients’ scores on the internalized stigmatization scale were compared with their employment status, it was found that those who were unemployed scored higher on social withdrawal than those who were working.Conclusion: As the patients’ scores on internalized stigmatization and the internalized stigmatization subscales increased, their quality of life decreased.
Keywords: Alcohol and substance dependence; dependence, internalized stigmatization; quality of life